A construção dos números naturais: um foco nas quatro operações fundamentais - Sousa, Pedro Sérgio Sales de (2014)
This paper aims to present the construction of the natural numbers and the axiomatic definition with respect to the four fundamental operations for students and teachers of elementary school.To this was presented a sequence initially addressing on the study of mathematics, the concept of mathematics, mathematical knowledge and a mathematical brief history to see how mathematical theories and practices are designed, developed and used in a specific context of each era. The second moment was described the construction of natural numbers through the Peano axioms, continuing with the rigorous definition of each operation and ending with the order relation in the set of natural numbers.